The Status of Yemini Women : From Aspiration to Opportunity - World Bank (Washington, DC, 2014)
The report draws on the conceptual framework of the world development 2012: gender equality and development, and the regional report on gender equality, opening doors: gender equality in the Middle East and North Africa. The report's analytic approach is unique in threading together three bodies of evidence and analysis to shed new light on significant trends and causes underpinning the large gender disparities in the country. The report presents: i) a fresh look at available survey data on human development and socio-economic indicators in the country; ii) a brief history and in-depth analysis of the most critical legal barriers to women's and girl's full participation in Yemeni society; and iii) insights from a rich qualitative dataset collected in January 2011.The findings especially highlight the powerful roles of social norms and legal rights and entitlements in placing women and girls at a disadvantage and constraining not only faster progress on gender equality but also the country's economic development. The objectives of this report are two-fold: first, to take stock of the status of gender outcomes in Yemen and understand the forces that are driving the strong gender inequalities; and second, drawing on these insights and outcomes of the study, to highlight promising areas for policy action in this crucial transition period. The report explores how individual aspirations and opportunities in the areas of education, family formation, and labor force participation are constrained by the severe gender gaps in Yemeni society.